ANALISIS RANTAI NILAI (VALUE CHAIN) PRODUK PINANG (ARECA CATECHU L) DI KOTA MANOKWARI (VALUE CHAIN ANALYSIS OF ARECA NUT (ARECA CATECHU L) PRODUCTS IN MANOKWARI CITY - Agus Setyawati Herinda Asmara Jati; Kunto Wibowo; Ludia T. Wambrauw (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2021)
The high demand for areca nut makes it a product that has good economic opportunities, however local areca nut production in West Manokwari District has not been able to meet this need. The purpose of this research is to find out who are the actors in the areca value chain, the map of the areca value chain, and the problems and potentials of areca value chain development. The method used in this research is descriptive qualitative and quantitative analysis. Based on the results of the research, the value chain actors are betel nut farmers, wholesalers, market collectors, retailers, and consumers. Problems in the areca value chain are traditional areca nut cultivation techniques, no processing of areca products, and the determination of the price for areca nut at the farmer level, which is still based on the farmer's assessment without a standard unit (kilogram). Potential development is the optimization of cultivation techniques, creating independent areca nut processed products, determining the price of areca nuts according to the standard unit.